3D printing of food materials: A state of art review and future applications. (2020) - Piyush,; Kumar, Raman; Kumar, Ranvijay
Abstract: 3D printing is also known as additive manufacturing is one of the most accurate fabrication techniques which covers potential applications in almost all industrial/commercial/households fields. A wide variety of materials are reported in last 2–3 decades for fabrication of functional/non-functional structures, but scope is limited to few studies in the field of food printing. This paper is a state of art review for different 3D printing process, processing techniques and materials available for food printing. In addition, review has been made about nourishment/food materials that can be 3D printed with redid flavour, shape and altered substance and constituents can be printed. This paper also concludes future aspects of 3D food printing for improvement in processing and design.